2019
DOI: 10.3389/fphys.2019.00458
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Regulator of Preadipocyte Differentiation, Transcription Factor TCF21, Functions Partially Through Promoting LPL Expression

Abstract: The transcription factor TCF21 has been previously shown to be specifically expressed in white preadipocytes in mice. However, the exact biological function of TCF21 in the context of adipogenesis remains unknown. In the current study, we used chicken lines selected based on their abdominal fat content, and observed a significant decrease in TCF21 mRNA and protein levels in the abdominal fat of lean broilers relative to fat broilers. Moreover, TCF21 expression increased throughout preadipocyte differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…The thymidine kinase ( TK ) minimal promoter with 3 copies of the DR1 element (AGGTCAAAGGTCA) at its 5′ end was synthesized by GENEWIZ and cloned into the pGL3-Basic Luciferase Reporter Vector (Promega) to yield the 3xPPRE-TK-Luc reporter construct. The CCAAT/enhancer-binding protein alpha ( C/EBPα ), fatty acid synthase ( FAS ), adipocyte fatty acid–binding protein ( A-FABP ), lipoprotein lipase ( LPL ), and perilipin 1 ( PLIN1 ) promoter reporters containing the potential PPRE were previously generated by our laboratory ( Zhang et al., 2014 ; Zhang et al., 2019 ). The full-length PPARγ1 (NM_001001460.1) was amplified from the pooled chicken cDNA using PCR with the following primers: PPARγ1 -F (5′-GGAATTCATGGTTGACACAGAAATGCCGT-3′) and PPARγ1 -R (5′-CCTCGAGGAGGATAAGAACTACTATCGCC-3′) and introduced into the Eco RI and Xho I sites of a pCMV-HA vector to yield pCMV-HA-PPARγ1.…”
Section: Methodsmentioning
confidence: 99%
“…The thymidine kinase ( TK ) minimal promoter with 3 copies of the DR1 element (AGGTCAAAGGTCA) at its 5′ end was synthesized by GENEWIZ and cloned into the pGL3-Basic Luciferase Reporter Vector (Promega) to yield the 3xPPRE-TK-Luc reporter construct. The CCAAT/enhancer-binding protein alpha ( C/EBPα ), fatty acid synthase ( FAS ), adipocyte fatty acid–binding protein ( A-FABP ), lipoprotein lipase ( LPL ), and perilipin 1 ( PLIN1 ) promoter reporters containing the potential PPRE were previously generated by our laboratory ( Zhang et al., 2014 ; Zhang et al., 2019 ). The full-length PPARγ1 (NM_001001460.1) was amplified from the pooled chicken cDNA using PCR with the following primers: PPARγ1 -F (5′-GGAATTCATGGTTGACACAGAAATGCCGT-3′) and PPARγ1 -R (5′-CCTCGAGGAGGATAAGAACTACTATCGCC-3′) and introduced into the Eco RI and Xho I sites of a pCMV-HA vector to yield pCMV-HA-PPARγ1.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro , Tcf21 increased pre-adipocyte differentiation, whereas Tcf21 knockdown and overexpression attenuated and promoted pre-adipocyte differentiation, respectively, which changed lipid droplet accumulation. Moreover, ChIP and luciferase analyses showed that TCF21 controls the transcription of lipoprotein lipase (LPL) by directly binding to the E-box motif in the Lpl promoter ( 62 ).…”
Section: Tcf21 In the Development Of Other Tissuesmentioning
confidence: 99%
“…Therefore, chicken was considered a more suitable model for non-alcoholic fatty liver disease (NAFLD). Enough studies have revealed the details about lipid synthesis, especially the enzymes of lipid synthesis, such as ACC, FAS, and LPL (Mottillo et al, 2017;Seo et al, 2018;Zhang et al, 2019;Bhat et al, 2021). Meanwhile, many studies have concluded that adult chicken fat tissue has no or very weak lipid synthesis ability (Na et al, 2018).…”
Section: Discussionmentioning
confidence: 99%